Ozonated water treatment for sustaining quality attributes and prolonging shelf life in grapes - Chinnasamy, K; Balachandran, A; Borthakur, P; Venkatachalam, S; Kolandasamy, P (Plant Science Today, 2025)
Grapes (Vitis vinifera), a subtropical fruit crop, are highly valued for their nutritional composition and global economic importance, both as fresh consumption and processed forms. However, postharvest quality loss, primarily caused by grey mould (Botrytis cinerea), microbial decay and physiological weight loss, poses a significant challenge to grape storage and marketability. This experiment was designed to evaluate the efficacy of postharvest ozonated water treatment on quality attributes and extending the shelf life of grapes. Grape bunches were subjected to four treatments: control (no dip) and immersion in 0.3 ppm ozonated water for 5, 10 and 15 min, followed by storage at 4±2°C and 90 % relative humidity (RH). Results indicated significant improvements in key quality parameters for grapes treated with ozonated water, particularly with the 15 min treatment (T4). These bunches exhibited higher titratable acidity (0.24 %), ascorbic acid content (1.81 mg/100 g), and firmness (4.80 N) while exhibiting 21.82 % lower physiological weight loss compared to the control. Ozonated water treatment also minimized berry abscission (3.77 %) and maintained sensory properties. The sugar-acid ratio was highest (84.72) in 5 min treatment group (T2) on the 36th day of storage, enhancing flavour attributes. Significantly, T4 extended the shelf life of grapes to 39.84 days, nearly five days longer than the untreated grapes. This study demonstrated the potential of ozonated water as an eco-friendly, residue-free technology for postharvest preservation, offering a safer alternative to chemical fumigation. The findings support the integration of ozonated water treatments into grape postharvest management practices to enhance quality, storability and consumer acceptability.